The Reovirus Protein μ2, Encoded by the M1 Gene, Is an RNA-Binding Protein - Brentano, Liana (American Society for Microbiology, 1998)
The reovirus M1, L1, and L2 genes encode proteins found at each vertex of the viral core and are likely to form a structural unit involved in RNA synthesis. Genetic analyses have implicated the M1 gene in viral RNA synthesis and core nucleoside triphosphatase activity, but there have been no direct biochemical studies of μ2 function. Here, we expressed μ2 in vitro and assessed its RNA-binding activity. The expressed μ2 binds both poly(I-C)- and poly(U)-Sepharose, and binding activity is greater in Mn(2+) than in Mg(2+). Heterologous RNA competes for μ2 binding to reovirus RNA transcripts as effectively as homologous reovirus RNA does, providing no evidence for sequence-specific RNA binding by μ2. Protein μ2 is now the sixth reovirus protein demonstrated to have RNA-binding activity.